Development of Mobile Learning Based on Block Programming Android as a Source of Basic Learning - Royani, Ida; Nurjaman, Muhamad Ichsan; Akbar, Al Juska Sasni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to develop mobile learning-based learning resources with Android block programming approach to improve the effectiveness of learning management in basic education. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). In the Define stage, a needs analysis of students and teachers in the use of mobile technology for learning is conducted. The Design stage includes designing an interactive, block programming-based mobile application that is easy to use by educators and learners. Furthermore, the Develop stage involves making a prototype of the application as well as limited trials to assess its feasibility and effectiveness. In the Disseminate stage, the application was tested more widely and socialized to users with further evaluation. The results show that block programming-based mobile learning can increase learning interactivity, improve learning resource management, and increase student involvement in the learning and playing process. The implication of this research contributes to innovation in the digitalization of learning management that is relevant to the development of educational technology in the digital era.